CONSCIOUS LEADERSHIP: REFLECTIONS BASED ON THE LIFE AND WORK OF LUIS BEDOYA REYES AND VICTOR RAÚL HAYA DE LA TORRE - Llerena, V. Herly (2020)
The main characteristic of great leaders is their ability to perceive the depth of their inner world and interact with the surrounding universe. In terms of this characteristic, in Peru there are two historic figures that stand out:  Luis Bedoya Reyes and Víctor Raúl Haya de la Torre. These two men possessed higher levels of consciousness. There are 11 different levels of consciousness, considered as permanent features, and which are classified according to the spectrum of colors, from infrared to clear light. Peruvian politics is at low levels of consciousness, and conscious leadership can be a very effective, advantageous, and practical means to reach higher levels of consciousness, both in the field of politics, as well as in companies and organizations of all kinds.